MENINGKATKAN KEMAMPUAN MEMBACA MELALUI PEMANFAATAN TULISAN SINGKAT BRAILLE BAGI SISWA TUNANETRA - tumirah, tumirah (Pendidikan Luar Biasa, 2013)
The aim of the study is improving fourth grade visual handicaped students? reading ability simester I in SLB Negeri 1 pemalang using braille reading text. The method of the study was classroom action research and the subject of the reseach was 2 person of visual handicaped students. Data collecting method used test, documentation and observation. The data analysis was comparative descriptive by comparing the results between cycles. The result indicates that student?s initial capability in reading was 48,18. The improvement occured after 2 cycles using short braille reading text. Students? reading score on the second cycle was 78,5. The conclusion of the reseach indicated that short braille reading text improved the fifth grade of visual handicaped student?s short reading text in the 1st simester of SLB Negeri 1 Pemalang 2012/2013. Keywords: visual handicaped, Braille, reading, tusing